Genetic polymorphisms associated with upper gastrointestinal bleeding: a systematic review - Forgerini, Marcela [UNESP]; Lucchetta, Rosa Camila [UNESP]; Urbano, Gustavo; de Nadai, Tales Rubens; de Carvalho Mastroianni, Patrícia [UNESP] (Springer Nature, 2021)
Non-variceal upper gastrointestinal bleeding (non-variceal UGIB) is a frequent and severe adverse drug reaction. Idiosyncratic responses due to genetic susceptibility to non-variceal UGIB has been suggested. A systematic review was conducted to assess the association between genetic polymorphisms and non-variceal UGIB. Twenty-one publications and 7134 participants were included. Thirteen studies evaluated genetic polymorphism in patients exposed to non-steroidal anti-inflammatory drugs, low-dose aspirin, and warfarin. Eight studies present at least one methodological problem. Only six studies clearly defined that the outcome evaluated was non-variceal UGIB. Genetic polymorphisms involved in platelet activation and aggregation, angiogenesis, inflammatory process, and drug metabolism were associated with risk of non-variceal UGIB (NOS3, COX-1; COX-2; PLA2G7; GP1BA; GRS; IL1RN; F13A1; CDKN2B-AS1; DPP6; TBXA2R; TNF-alpha; VKORC1; CYP2C9; and AGT). Further well-designed studies are needed (e.g., clear restriction to non-variceal UGIB; proper selection of participants; and adjustment of confounding factors) to provide strong evidence for pharmacogenetic and personalized medicine.